Reliability and validity of the Readiness for Hospital Discharge Scale in patients with spinal cord injury - Jacques S. De Lange; Jolandi Jacobs; Nadine Meiring; Boitumelo Moroane; Tinei Verster; Steve Olorunju; Mokgadi K. Mashola (AOSIS, 2020)
Background: Measuring rehabilitation outcomes in patients with spinal cord injury (PWSCI) requires measurement tools that are valid and reliable and have been psychometrically tested in the population with spinal cord injury (SCI). The Readiness for Hospital Discharge Scale (RHDS) has been found to be reliable and valid in adult surgical patients, post-partum mothers, parents of hospitalised children and geriatrics. However, the psychometric properties have not yet been tested in the population with SCI, furthermore, in a South African context. Objectives: The purpose of this study was to psychometrically test the internal consistency and construct validity of the RHDS as a measure of discharge readiness in PWSCI prior to discharge from rehabilitation units in the Tshwane metropolitan area, South Africa. Method: A cross-sectional study that included 50 PWSCI who were in their last week of rehabilitation was conducted. The RHDS item and scale statistics were calculated by using descriptive statistics and the scale reliability was measured for internal consistency by using Cronbach's alpha coefficients. To determine construct validity, convergent and divergent validities were measured by using the RHDS items' correlation coefficient dimensions. All data were tested at the 0.05 level of significance by using Statistics and Data (STATA) statistical software, version 14. Results: Cronbach's alpha of the RHDS was 0.904, indicating an excellent reliability coefficient. Convergent validity scores showed 81% correlation coefficients, although divergent validity scores showed 62% correlation coefficients. Conclusion: The RHDS is a valid and reliable measure of readiness for discharge in a South African sample of PWSCI and can be used in SCI rehabilitation. Clinical implications: Over and above using the RHDS to determine if PWSCI are ready for discharge in the clinical setting, the RHDS may also assist health care practitioners to assess the patient's progress towards readiness and strategies for addressing shortcomings to meet short and long-term goals of the rehabilitation process.